2014
DOI: 10.1007/s13244-014-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT pitfalls in oncological head and neck imaging

Abstract: ObjectivesPositron emission tomography-computed tomography (PET/CT) with fluorine-18-fluorodeoxy-D-glucose (FDG) has evolved from a research modality to an invaluable tool in head and neck cancer imaging. However, interpretation of FDG PET/CT studies may be difficult due to the inherently complex anatomical landmarks, certain physiological variants and unusual patterns of high FDG uptake in the head and neck. The purpose of this article is to provide a comprehensive approach to key imaging features and interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 66 publications
(183 reference statements)
4
179
0
2
Order By: Relevance
“…Furthermore, symmetrical tracer uptake of Waldeyer's ring, the salivary glands, and the thyroid without morphologic correlate is frequently observed and does not indicate an underlying pathology (23,24). Another frequent cause for symmetrical tracer uptake is brown fatty tissue (22,25). Due to excellent spatial registration of the CT and MRI images and the PET dataset, symmetrical tracer uptake could be attributed precisely to the corresponding tissue in this study by PET/CT and PET/MRI.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, symmetrical tracer uptake of Waldeyer's ring, the salivary glands, and the thyroid without morphologic correlate is frequently observed and does not indicate an underlying pathology (23,24). Another frequent cause for symmetrical tracer uptake is brown fatty tissue (22,25). Due to excellent spatial registration of the CT and MRI images and the PET dataset, symmetrical tracer uptake could be attributed precisely to the corresponding tissue in this study by PET/CT and PET/MRI.…”
Section: Discussionmentioning
confidence: 63%
“…Although Choi et al (28) found increased focal tracer uptake to be a strong predictor for malignancy, more recent studies showed that also benign nodules show a strong tracer uptake and that the frequency of malignant nodules is lower than initially reported (29). Still, focal asymmetrical 18 F-FDG uptake in the thyroid demands further investigation (25,29,30). Unfortunately, MRI is not superior to CT in the differentiation between benign and malignant thyroid lesions (31).…”
Section: Discussionmentioning
confidence: 96%
“…Most common places of the infection/inflammation such as oropharyngeal, laryngeal, and middle ear infections can also affect the LNs in the neck, resulting in increased FDG uptake [23]. This can cause misinterpretation that may lead to low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study fi ndings are limited as the PET/MRI examination protocol focused on the abdomen and pelvis and only included the chest if suspicious lesions were detected on the prior PET/CT scan. Furthermore, PET/MRI detected more suspicious lesions, but there was no fi nal histopathological correlation to exclude false-positive and false-negative fi ndings which are known to occur in hybrid imaging [ 42 ]. Advantages of PET/MRI include the lack of ionizing radiation for the MRI component, which makes it an attractive tool for repeated examinations, particularly in younger patients.…”
Section: Hybrid Imaging For Suspected Prostate Carcinomamentioning
confidence: 99%